Weather parameters and biotic factors synergistically shape the phyllosphere microbiome of pomelo (Citrus maxima (Burm.) Merr.) across annual cycle - Yuan, Weina; Qin, Yongqiang; Zhang, Wei; Zhou, Wenqian; Feng, Guangda; Zhu, Honghui; Yao, Qing (Frontiers in Plant Science, 2025)
Phyllosphere microbiome plays important roles in crop adaptation to the changing environments. Perennial woody crops undergo annual cycles with the changing weather parameters and the biological factors, which might shape the phyllosphere microbial community. In this study, we aimed to investigate the dynamics of phyllosphere microbiome of pomelo (Citrus maxima (Burm.) Merr.), an economically important horticultural crops worldwide, and to compare the respective contribution of the weather parameters and the biotic factors to the microbial community assembly, with special focus on the amino acids in leaves. Hi-Seq analysis revealed that both bacterial and fungal communities showed annual cycle dynamics, and the bacterial community in summer was much different from those in other seasons probably due to high temperature and precipitation. However, contribution of the biotic factors (e.g., leaf traits) (12%-29%) to microbial community assembly was higher than that of the weather parameters (4%-15%). Redundancy analysis indicated that the leaf amino acids significantly affected bacterial community while sugars significantly affected fungal community, highlighting the differential patterns of bacterial and fungal community as affected by the biotic factors. Finally, structure equation model showed that the weather parameters influenced microbial community colonizing pomelo leaves both in a direct way and in an indirect way via leaf traits (mainly amino acids). These results demonstrate the primary role of weather parameters and the key role of leaf amino acids in shaping phyllosphere microbiome.